ANALYSIS OF KNOWLEDGE OF TAXATION REGULATIONS, TAX AWARENESS AND PERFORMANCE OF ACCOUNT REPRESENTATIVE (AR) ON TAX MANDATORY COMPLIANCE - Leli Mulyani; Asep Kurniawan; Indah Umiyati (Journal of Taxation Analysis and Review, 2019)
The purpose of this research is to (1) know the effect of tax regulation on taxpayer compliance, (2) influence of tax awareness to taxpayer compliance, (3) influence of Account Representative performance moderate between knowledge of taxation regulation to taxpayer compliance, and (4) Account Representative performance between tax awareness of taxpayer compliance. This research approach using quantitative method, while data analysis using descriptive data analysis. Population and samples in this study are individual taxpayers registered in KPP Pratama Subang, with the number of samples of 100 respondents. Sample selection technique in this research use incidental sampling technique. The data used in this study is primary data, primary data obtained from the distribution of questionnaires to individual taxpayers registered in KPP Pratama Subang. Data analyzed using stepwise regression analysis method and hypothesis test using Statistical Program from Society Science (SPSS) version 21. Based on the results of hypothesis testing in this study are (1) Knowledge of tax regulations have a positive effect on taxpayer compliance. (2) Tax awareness has a positive effect on tax compliance. (3) Account Representative performance does not reinforce the influence of tax regulation knowledge on taxpayer compliance. (4) Account Representative performance does not reinforce the influence of tax awareness on taxpayer compliance.